PENGARUH REPUTASI AUDITOR DAN ASIMETRI INFORMASI TERHADAP PERATAAN LABA DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2018) - Natasha Giovani Kusumaningtyas; Etty Murwaningsari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
Income smoothing is one of earnings management element. This research have purpose to analyze and examine empirical evidence of the influence of asymmetry information and auditor reputation on income smoothing with independent commissioners as a moderating variable and with variable control consisting of cash holding, institutional ownership, agency cost, managerial ownership and firm value. This research uses regression logistic with the resullt that the asymmetry information and auditor reputation have an effect on income smoothing. Whereas an independent commissioner as a moderating variable shows that the independent commissioner is proven to weaken the positive influence of asymmetry information on income smoothing, but independent commissioner is not proven to substantiate the negative effect of the auditor's reputation on income smoothing.